Speed control of brushless dc motor using pid controller - Zahari, Musab (2022)
Brushless direct current (BLDC) motors are extensively utilized in a variety of industrial applications due to their high efficiency, high torque, and durability. However compared to conventional direct current motors, BLDC motor design requires a suitable controller for accurate speed and position control for its implementation. The goal of this study is to create a full model of the BLDC motor as well as suitable controller for its speed tracking control within the predefined performance parameters. Although several controller schemes have been proposed, most are complex and require tedious computations. Due to its simplicity and ease of implementation, a Proportional Integral Derivative (PID) controller was used as the basis for the speed controller. The BLDC motor as well as the speed controller was simulated using MATLAB-Simulink software and the speed tracking simulation performance was then compared against experimental data using Hardware-in-Loop simulation. The experimental and simulation results indicate that the proposed controller achieves excellent speed tracking performance within the set performance objectives.